A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Franzsen, R.C.D. (Riel) (University of Pretoria, 2018)
Thesis (LLD)--University of Pretoria, 2018.